2004
DOI: 10.1542/peds.2003-1038-l
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interventions to Prevent Childhood Farm Injuries

Abstract: ABSTRACT. Objective. The goal of the study was to systematically review the global body of evidence surrounding the effectiveness of interventions for the prevention of acute pediatric agricultural injuries. A specific focus was the effectiveness of the North American Guidelines for Children's Agricultural Tasks.Methods. Two reviewers independently screened studies and applied inclusion criteria on the basis of searches of 17 bibliographic databases (eg, Medline and Embase). We also screened reference lists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 27 publications
(55 reference statements)
2
80
1
Order By: Relevance
“…Other reviews of interventions to prevent childhood farm injuries concluded that there was insufficient evidence to draw firm conclusions on their effectiveness (25,26). Three other reviews on general farm safety interventions (�, 2�), and educational interventions (28) using less strict inclusion criteria than we used, also concluded that there was no evidence available.…”
Section: Other Reviewsmentioning
confidence: 94%
“…Other reviews of interventions to prevent childhood farm injuries concluded that there was insufficient evidence to draw firm conclusions on their effectiveness (25,26). Three other reviews on general farm safety interventions (�, 2�), and educational interventions (28) using less strict inclusion criteria than we used, also concluded that there was no evidence available.…”
Section: Other Reviewsmentioning
confidence: 94%
“…Any differences between the researchers were resolved by discussion. Quality scores of 21 and higher were considered good, 11 to 20 -moderate and 10 and lower -poor (Hartling et al, 2004).…”
Section: Data Extraction Analysis and Assessmentmentioning
confidence: 99%
“…Within the Acute Exercise group, the Down and Black Tool scores ranged from 10 to 19 out of 27 (limited to moderate methodological strength). [46][47][48] The lone RCT 49 categorized within the Non-Acute Exercise group received a PEDro Scale score of six out of 10 (good methodological quality), 50 whereas the remaining studies ranged from 10 to 20 out of 27 on the Down and Black Scale (considered limited to moderate methodological quality). 46 Acute exercise techniques Fourteen papers investigated the vascular effects of a single acute exercise bout.…”
Section: Resultsmentioning
confidence: 99%